2019
DOI: 10.3991/ijac.v12i3.11067
|View full text |Cite
|
Sign up to set email alerts
|

Developing Complex Problem-Solving Skills: An Engineering Perspective

Abstract: While technical skills remain the core foundation for engineering graduates, professional competencies, including communication, teamwork, and complex problem solving, are increasingly important to succeed in work environments. To enhance the employability of our students, we have integrated several professional skills courses into our “Software Design and Engineering” Master study curriculum, and combined each of them with a technical course. In this paper, we present a blended-learning course design includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The dual features of the learning objectives are contrasted with the contextual approach, which implies the choice of the educational content with a higher degree of the necessary material for the implementation of a given type of activity. The structure of the course is developed based on the type of activity [17,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dual features of the learning objectives are contrasted with the contextual approach, which implies the choice of the educational content with a higher degree of the necessary material for the implementation of a given type of activity. The structure of the course is developed based on the type of activity [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…The comparative analysis showed that the concept of the occupational skills model is characterized by the systemic and activity approach, the well-structured terminological apparatus, a clearly defined process of designing modular technologies, and a detailed study of the types of educational and program documentation [33,34]. There is a range of pedagogical technologies that can provide the proper level of training in a corporate training center; however, the concept of the occupational skills model, which can ensure the flexibility of the educational process and an increased quality of the development of professional competencies, meets the goals and requirements of the customer to the greatest extent [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the last module, the students apply their complex problem solving skills on a concrete software integration project. A detailed description of this concept can be found in [5].…”
Section: Modulementioning
confidence: 99%